Pengaruh Penerapan Model Pembelajaran Interactive Lecture Demonstrations (ILDs) Terhadap Kemampuan Pemahaman Konsep Fisika Siswa - Petri Reni Sasmita; Halimatus Sakdiah; Zainal Hartoyo (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the effect of Interactive Lecture Demonstrations (ILDs) learning models on students' understanding of physics concepts. The research method used was a preliminary experimental research method with a one-group pretest-posttest design that was carried out in class XI students in one of the high schools (SMA) in Kerinci Regency. The sampling technique uses a cluster sampling method. Data collection uses a pre-test and a post-test to measure students' understanding of physics concepts. The results of the calculation of the effect size indicate that the application of learning with Interactive Lecture Demonstrations (ILDs) models has a major effect on the ability of understanding students' physics concepts. The effect size calculation in this study was carried out using the Cohen formula. From the calculation results obtained effect size score of 0.81. This score is in the big category. This shows that the application of the Interactive Lecture Demonstrations (ILDs) learning model has a big influence on students' conceptual understanding ability. Thus, it can be concluded that the application of Interactive Lecture Demonstrations (ILDs) models in learning physics has a great influence on the ability of understanding students' physics concepts.